Stability of Anti-Insect Ingredient from Jayanti Plants (Sesbania sesban) for Integrated Control of Cabbage Pest - Suripto Suripto; Hilman Ahyadi; Rachmawati Noviana Rahayu; Lalu Japa (Jurnal Penelitian Pendidikan IPA, 2023)
The specific purpose of this study was to determine the stability of S. sesban insecticide during storage before application and its stability in water during application. The dry powder of S. sesban leaves was extracted using water as the single solvent. Bioassay of S. sesban leaf extract was carried out on cabbage caterpillars (Plutella xylostella larvae) and Diadegma semiclausum imago on cabbage plants using a variation of storage time design. Mortality data of P. xylostella larvae and D. semiclausum imago were respectively processed by probit analysis to determine LC50. The results showed that the insect repellent content of S. sesban leaves was a compound from the saponin group and was unstable during simplicia storage, extract storage and also unstable in water before and during application. Storage of S. sesban leaf simplicia from 1 to 3 months only slightly reduced the lethal toxicity of the extract to P. xylostella larvae (mortality from 95 to 80% or LC50 from 28.82 to 28.83 ppm), but after 6 to 12 months storage, the lethal toxicity decreased drastically (mortality was 12.5 to 1.25% and LC50 was 247.99 ppm until calculated). Storage of S. sesban leaf extract from 7 to 15 days had resulted in a sharp decrease in lethal toxicity to P. xylostella larvae (mortality 70 to 40% and LC50 34.05 to 59.43 ppm) and 30 days storage causes the insect repellent to be inactive. (mortality was only 1.25% and LC50 was unaccounted for). Exposure to a solution of S. sesban leaf extract for 24 to 48 hours caused a decrease in lethal toxicity to P. xylostella larvae (mortality 32 to 28% and LC50 62.63 to 64.85 ppm) and after the solution was stored for 72 hours, the insect repellent was almost no active again (mortality was only 1.25 and LC50 was unstoppable). All storage treatments of insect repellent from S. sesban leaves showed no significant difference in the effect of lethal toxicity on D. semiclausum imago. In all the results of the bioassays, the mortality of D. semiclasum was 0 to 1.25% and each of all LC50(s) was unaccounted for